International Perspectives on the Practical Application of Violence Risk Assessment: A Global Survey of 44 Countries - Singh, Jay P. (2014)
Mental health professionals are routinely called upon to assess the risk of violence presented by their patients. Prior surveys of risk assessment methods have been largely circumscribed to individual countries and have not compared the practices of different professional disciplines. Therefore, a Web-based survey was developed to examine methods of violence risk assessment across six continents, and to compare the perceived utility of these methods by psychologists, psychiatrists, and nurses. The survey was translated into nine languages and distributed to members of 59 national and international organizations. Surveys were completed by 2135 respondents from 44 countries. Respondents in all six continents reported using instruments to assess, manage, and monitor violence risk, with over half of risk assessments in the past 12 months conducted using such an instrument. Respondents in Asia and South America reported conducting fewer structured assessments, and psychologists reported using instruments more than psychiatrists or nurses. Feedback regarding outcomes was not common: respondents who conducted structured risk assessments reported receiving feedback on accuracy in under 40% of cases, and those who used instruments to develop management plans reported feedback on whether plans were implemented in under 50% of cases. When information on the latter was obtained, risk management plans were not implemented in over a third of cases. Results suggest that violence risk assessment is a global phenomenon, as is the use of instruments to assist in this task. Improved feedback following risk assessments and the development of risk management plans could improve the efficacy of health services. © 2014 Copyright International Association of Forensic Mental Health Services.